2014
DOI: 10.4103/0974-9233.134668
|View full text |Cite
|
Sign up to set email alerts
|

Repeat selective laser trabeculoplasty can be effective in eyes with initial modest response

Abstract: Purpose:To evaluate the effectiveness of repeat selective laser trabeculoplasty (SLT) in eyes exhibiting only a modest response upon initial treatment.Materials and Methods:Retrospective chart review was conducted of 51 eyes that received initial 360 degree SLT (SLT1) and subsequent SLT (SLT2) from 2003-2011 at a large academic ophthalmology practice. Successful response (S) was a post-treatment 12 month mean IOP reduction ≥20% from baseline, while modest response (M) was <20% reduction over the same time. Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Similar IOP reduction and success rates have been observed with repeat SLT compared with initial SLT in retrospective studies. [352][353][354] The safety profile of SLT appears to be good, with mild anterior chamber inflammation after treatment and less ocular discomfort compared with ALT. 346 Intraocular pressure spikes have been noted after SLT in 4.5% to 27% of eyes in various studies, 343,347,351,355 which are similar to rates observed with ALT.…”
Section: Laser Trabeculoplastymentioning
confidence: 99%
“…Similar IOP reduction and success rates have been observed with repeat SLT compared with initial SLT in retrospective studies. [352][353][354] The safety profile of SLT appears to be good, with mild anterior chamber inflammation after treatment and less ocular discomfort compared with ALT. 346 Intraocular pressure spikes have been noted after SLT in 4.5% to 27% of eyes in various studies, 343,347,351,355 which are similar to rates observed with ALT.…”
Section: Laser Trabeculoplastymentioning
confidence: 99%
“…In 2013, Avery et al 7 found that repeat 360° SLT has similar efficacy to primary 360° SLT with respect to reduction in IOP and success rates (IOP reduction of ≥20% from an individually determined target IOP), producing a longer duration of treatment success. In 2014, Khouri et al 10 reported that initial and repeat SLT significantly reduced IOP and the success of repeat SLT was independent of the response to initial SLT and produced an effective IOP reduction for up to 24 months 9…”
Section: Discussionmentioning
confidence: 99%
“…Repeatability of SLT has been studied and considered feasible in suitable patients requiring further IOP reduction. [7][8][9][10][11][12][13][14] However, many of these studies are retrospective and limited by small sample sizes and lack predefined retreatment criteria. In addition, in all but 1 of these studies, 13 SLT was used as an adjunctive treatment in patients already receiving topical IOP-lowering treatment.…”
mentioning
confidence: 99%